Analisis Manajemen Pendidikan Karakter Terhadap Pembinaan Akhlak Peserta Didik MIS Cendikia Insani Al-Washliyah Sukamandi Hulu - Indri Febrianti; M. Padeli Wibowo; Ahmad Rifai; Aisyah Oktaviana; Nanjah Fachira Ayundari; Malika Aulia Husnah Saragih; Tengku Darmansah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research discusses the role of character education management in shaping the morals of students at MIS Cendikia Insani Al-Washliyah Sukamandi Hulu. The research background highlights the urgent need for character formation amidst the complexity of global challenges. The aim of the research is to analyze the influence of character education management on the moral development of students. The research method uses a qualitative approach and library research involving researchers as key instruments. Data was collected through interviews and content analysis, with research carried out at MIS Cendikia Insani Al-Washliyah Sukamandi Hulu. It is hoped that the research findings will provide in-depth insight into the implementation of character education management in the school. The implications of this research include recommendations for expanding data collection methods, involving the perspectives of parents and students, and detailing the steps of the character education management model. It is hoped that the research results can provide a concrete basis for developing a more effective character education program at MIS Cendikia Insani Al-Washliyah Sukamandi Hulu.